Expression of myogenic regulatory factors in chicken embryos during somite and limb development - Mok, Gi Fay; Mohammed, Rabeea Hazim; Sweetman, Dylan (Wiley, 2015)
The expression of the myogenic regulatory factors (MRFs), Myf5, MyoD, myogenin (Mgn) and MRF4 have been analysed during the development of chicken embryo somites and limbs. In somites, Myf5 is expressed first in somites and paraxial mesoderm at HH stage 9 followed by MyoD at HH stage 12, and Mgn and MRF4 at HH stage 14. In older somites, Myf5 and MyoD are also expressed in the ventrally extending myotome prior to Mgn and MRF4 expression. In limb muscles a similar temporal sequence is observed with Myf5 expression detected first in forelimbs at HH stage 22, MyoD at HH stage 23, Mgn at HH stage 24 and MRF4 at HH stage 30. This report describes the precise time of onset of expression of each MRF in somites and limbs during chicken embryo development, and provides a detailed comparative timeline of MRF expression in different embryonic muscle groups.